An Example of a Stroke Unit Reshaping in the Context of a Regional Hub and Spoke System in the COVID-19 Era - Candeloro, Elisa; Carimati, Federico; Tabaee Damavandi, Payam; Princiotta Cariddi, Lucia; Banfi, Paola; Clemenzi, Alessandro; Gallazzi, Marco; Mauri, Marco; Rebecchi, Valentina; Baruzzi, Fabio; Giorgianni, Andrea; Tozzi, Matteo; et al. (Frontiers in Neurology, 2020)
During the outbreak of COVD-19, the Neurology and Stroke Unit (SU) of the hospital of Varese had to serve as a cerebrovascular hub for, meaning that its referral area has been doubled. The number of beds of the SUwas increased from 4 to 8.We took advantage from the stop to the out-patient clinics, and we reshaped our activity to guarantee a 24/7 liabilityfor the administration of rtPA(IVT) in the SU and for the admission of the patient as soon as the endovasculat treatment (EVT) was ended. In 42 days,46 stroke patients were admitted to our hospital, and the 26.7% of them underwent IVT and/or EVT, which means that we treated 0.38 patients per day; in a reference period of 3 years before COVID-19 these same figures had been 23.5 % and 0.23. None of the patients had a major complication following the procedures. All the patients fell in the reference time limits for treatment-related time periods, but for 1 (6.25%) patient who exceeded the upper limit for the door-to-groin puncture for about 10 min. None of the patients was or became SARS-COV2 positive. In conclusion we were able to manage the new hub and spoke system safely and without delays. The reshaping of the SU was made possible by the significant reduction of the out-patient activity. The consequences of this reduction are still unknown, but eventually this emergency will suggest to reconsider the management and the allocation of the health system resources.